Exploring the Influential Stimulators of Career Choice: An Empirical Assessment by Exploratory Factor Analysis - Sultana , Tahmina; Mahmud , Muhammad Kawsar (Asian Journal of Empirical Research, 2020)
The study aims to explore the stimulators that influence the students to choose a career among lots of options. The population of the current study comprises students of the Faculty of Business Administration, Bangladesh University of Professionals. SPSS was used to analyze the collected data. Principle component analysis and regression analysis were performed that exhibited the family influence, personal interests, self-efficacy, and economic aspects exerted great influence on the selection of career. The result of the analysis revealed that independents variables have a significant influence on career choice. The study made the following recommendation that students should provide freedom to express their interest, discuss with students very friendly, not put any kind of pressure, should not underestimate students’ decisions, etc. These outcomes could be utilized to make the students opt for the meticulous career path and excel in the expected domain.